By-laws formulation and enforcement in natural resource management: lessons from the highlands of eastern Africa. Issue 2 (2nd April 2016) - Mowo, Jeremias; Masuki, Kenneth; Lyamchai, Charles; Tanui, Joseph; Adimassu, Zenebe; Kamugisha, Rick
Abstract: Degradation of land, water and vegetation in the highlands of eastern Africa is on the increase in the face of the enforcement of natural resource management (NRM) policies and related by-laws. In this study, reasons behind the limited contribution of NRM by-laws in arresting degradation of natural resources in the highlands of Ethiopia, Tanzania and Uganda are presented, and opportunities to improve effectiveness identified. Using key informants' interviews, focus group discussions, workshops, case studies and literature review, it is shown that inadequate community participation in the process of by-laws formulation and enforcement is the main reason for the ineffectiveness of most NRM by-laws in the three countries. When communities are fully involved in the process of NRM by-laws formulation and enforcement and both conventional and indigenous by-laws enforcement mechanisms are adopted, incidences of abuse of natural resources were reduced by as much as 50% in some of the study sites.